2015
DOI: 10.1371/journal.pone.0115353
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and Genetic Alterations Affect the WWOX Gene in Head and Neck Squamous Cell Carcinoma

Abstract: Different types of genetic and epigenetic changes are associated with HNSCC. The molecular mechanisms of HNSCC carcinogenesis are still undergoing intensive investigation. WWOX gene expression is altered in many cancers and in a recent work reduced WWOX expression has been associated with miR-134 expression in HNSCC. In this study we investigated the WWOX messenger RNA expression levels in association with the promoter methylation of the WWOX gene and miR-134 expression levels in 80 HNSCC tumor and non-cancero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…This is consistent with findings that WWOX methylation correlates with poor prognosis of patients with ovarian cancer (47), head and neck cancer (58), and chorangiocarcinoma (59).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with findings that WWOX methylation correlates with poor prognosis of patients with ovarian cancer (47), head and neck cancer (58), and chorangiocarcinoma (59).…”
Section: Discussionsupporting
confidence: 92%
“…In 2009 Bouteille et al (12) reported that the tumor suppressor protein WWOX is a negative regulator of the Wnt/β-catenin pathway and inhibits the transcriptional activity of this pathway by preventing nuclear import of the Dvl proteins. In our previous study we showed that the WWOX gene is inactivated in HNSCC as a result of genetic or epigenetic alterations (16). Here, to investigate the effect of Wwox on the cellular localization of Dvl proteins in HNSCC we silenced the WWOX gene in the HET-1A cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the homozygous deletion of the WWOX gene its decreased or aberrant expression has also been reported in multiple human cancers (13)(14)(15)(16). In our previous study we have shown that the WWOX gene is inactivated in HNSCC as a result of genetic and epigenetic alterations (16). In the present study we aimed to investigate the association between Wwox and Dvl proteins in human HNSCC tumors and cell lines.…”
Section: Introductionmentioning
confidence: 88%
“…As many studies showed, miR-134 not only functions as a tumor repressor, but also acts as a cancer promoter. High expression of miR-134 contributes to head and neck carcinogenesis by targeting the WW Domain-Containing Oxidoreductase (WWOX) gene [34]. However, overexpression of miR-134 can inhibit the cell cycle progression of human human ovarian cancer stem cells and decrease the tumorigenicity in nude mice [35].…”
Section: Discussionmentioning
confidence: 99%